Molecular analysis of chromosome 11 deletions in aniridia-Wilms tumor syndrome. - van Heyningen, V (1985)
We describe five individuals who have constitutional deletions of the short arm of one chromosome 11, including all or part of the band p13. All of these individuals suffer from aniridia; two have had a Wilms tumor removed. We have established lymphoblastoid cell lines from these and in three cases constructed somatic cell hybrids containing the deleted chromosome 11. Analysis of DNA from the cell lines and hybrids with a cloned cDNA probe has shown that the catalase gene is deleted in four of five patients. The catalase locus must be proximal to the Wilms and aniridia-related loci. We have not detected a deletion of the beta-globin or calcitonin genes in any of these individuals; we conclude these genes are likely to be outside the region 11p12-11p15.4. In addition, we have used monoclonal antibodies in fluorescence-activated cell sorting analysis to measure expression in the hybrids of two cell surface markers encoded by genes that map to the short arm of chromosome 11. The genes for both of these are deleted in two individuals but are present in the individual with the smallest deletion.